2010
DOI: 10.1021/jm901775y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Phenyl-Substituted Benzimidazole Carboxamide Poly(ADP-Ribose) Polymerase Inhibitors: Identification of (S)-2-(2-Fluoro-4-(pyrrolidin-2-yl)phenyl)-1H-benzimidazole-4-carboxamide (A-966492), a Highly Potent and Efficacious Inhibitor

Abstract: We have developed a series of phenylpyrrolidine- and phenylpiperidine-substituted benzimidazole carboxamide poly(ADP-ribose) polymerase (PARP) inhibitors with excellent PARP enzyme potency as well as single-digit nanomolar cellular potency. These efforts led to the identification of (S)-2-(2-fluoro-4-(pyrrolidin-2-yl)phenyl)-1H-benzimidazole-4-carboxamide (22b, A-966492). Compound 22b displayed excellent potency against the PARP-1 enzyme with a K(i) of 1 nM and an EC(50) of 1 nM in a whole cell assay. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…The importance of interdomain communication in DNAdependent activation is also demonstrated by Trp318 mutations at the HD-WGR-Zn3 domain interfaces, resulting in a catalytically inactive PARP1 without affecting DNA binding . Notably, the HD subdomain, implicated as a focal point for interdomain communication, is an important CAT domain structural element defining the size of the inhibitor-binding pocket, and sometimes directly interacting with bound inhibitors (Iwashita et al, 2005;Penning et al, 2010).…”
Section: Structural Basis For Parp-dna Trappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of interdomain communication in DNAdependent activation is also demonstrated by Trp318 mutations at the HD-WGR-Zn3 domain interfaces, resulting in a catalytically inactive PARP1 without affecting DNA binding . Notably, the HD subdomain, implicated as a focal point for interdomain communication, is an important CAT domain structural element defining the size of the inhibitor-binding pocket, and sometimes directly interacting with bound inhibitors (Iwashita et al, 2005;Penning et al, 2010).…”
Section: Structural Basis For Parp-dna Trappingmentioning
confidence: 99%
“…(C) Superpositions of the 33 PARP1 CAT domain structures from PDB indicate that the D-loop residue, Tyr889, can assume multiple side-chain conformations. Binding of a rigid stereospecific inhibitor (e.g., talazoparib) may sterically restrict the side-chain flexibility (PDB IDs: 4PJT, 4GV7, 4HHY, 4HHZ, 4L6S, 4DQY, 3GN7, 3L3L, 3L3M, 3GJW, 2RD6, 1WOK, 1UK0, and 1UK1) Kinoshita et al, 2004;Iwashita et al, 2005;Miyashiro et al, 2009;Gandhi et al, 2010;Penning et al, 2010;Langelier et al, 2012;Gangloff et al, 2013;Lindgren et al, 2013;Ye et al, 2013;Aoyagi-Scharber et al, 2014). (Ruf et al, 1998) and well characterized as a sequence-diverse element in the PARP superfamily Papeo et al, 2013;Steffen et al, 2013), may also contribute to the protein dynamics of the CAT domain that are implicated in the putative inhibitor-induced reverse-allosteric signaling.…”
Section: Structural Basis For Parp-dna Trappingmentioning
confidence: 99%
“…The structure of the PARP-1 catalytic domain (Protein Data Bank [PDB] 3L3M) (Penning et al 2005) was modeled mimicking phosphorylation at Ser782, Ser785, and Ser786 and revealed that the increase in negative charge results in the formation of a 3:10 helix (Lee et al 2000), giving rise to a more open catalytic domain (Fig. 3E).…”
Section: Cdk2 Activates Parp-1 In Response To Hormone Treatmentmentioning
confidence: 99%
“…Next, (S)-2-(2-fluoro-4-(pyrrolidin-2-yl)phenyl)-lH-benzimidazole-4-carboxamide (A-966492) was identified as a compound with high potency against the PARP-1 enzyme, showing activity at a concentration of 1 nM. In addition, it was orally bioavailable and possessed good in vivo efficacy in a murine melanoma model (Penning et al, 2010). Other benzimidazole-4-carboxamide analogues as PARP-1 inhibitors with high cellular activity were also presented (Tong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%